2021
DOI: 10.1021/acs.jpcb.1c03043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cooperativity of Ligand–Residue Interactions Evaluated with the Fragment Molecular Orbital Method

Abstract: By the splendid advance in computation power realized with the Fugaku supercomputer, it has become possible to perform ab initio fragment molecular orbital (FMO) calculations for thousands of dynamic structures of protein–ligand complexes in a parallel way. We thus carried out electron-correlated FMO calculations for a complex of the 3C-like (3CL) main protease (Mpro) of the new coronavirus (SARS-CoV-2) and its inhibitor N3 incorporating the structural fluctuations sampled by classical molecular dynamics (MD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
(132 reference statements)
0
14
0
Order By: Relevance
“…Fedorov et al 13 performed MD simulations with FMO calculations for two ligands bound to a Trp‐cage mini‐protein and systematically averaged the FMO‐based interaction energies to evaluate the protein–ligand binding energies. Hatada et al 14,15 also found the significance of structural fluctuations in the IFIE analysis on a complex system of SARS‐CoV‐2 main protease and N3 ligand. However, these studies have not addressed the ability of systematically averaged FMO‐based interaction energies to improve protein–ligand binding affinity predictions using a set of multiple candidate compounds.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Fedorov et al 13 performed MD simulations with FMO calculations for two ligands bound to a Trp‐cage mini‐protein and systematically averaged the FMO‐based interaction energies to evaluate the protein–ligand binding energies. Hatada et al 14,15 also found the significance of structural fluctuations in the IFIE analysis on a complex system of SARS‐CoV‐2 main protease and N3 ligand. However, these studies have not addressed the ability of systematically averaged FMO‐based interaction energies to improve protein–ligand binding affinity predictions using a set of multiple candidate compounds.…”
Section: Introductionmentioning
confidence: 92%
“…Fedorov et al 13 performed MD simulations with FMO calculations for two ligands bound to a Trp-cage mini-protein and systematically averaged the FMO-based interaction energies to evaluate the protein-ligand binding energies. Hatada et al 14,15 also found the significance of structural fluctuations in the IFIE analysis on a complex system of SARS-CoV-2 main protease and N3 ligand.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Then, for performing structural alignment, the intersection of residues involved in the formation of two antiparallel β-barrels between domains I and II for all monomers of M pro which contains 66 residues were selected based on "SHEET" records in the PDB files (See Table S2 for a list of residues contributing to the β-barrel structures). All M pro structures were aligned on the Cα atoms of the selected residues of a reference structure (6 LU7 chain A, the first released protein crystal structure for SARS-CoV-2 M pro in complex with a covalently bonded inhibitor N3, which has been analyzed and characterized in many experimental and computational studies 1,4,18,21,[41][42][43][44][45][46][47][48][49][50] ). The pairwise RMSD values for all above Cα atoms between every pair of the aligned protein structures did not exceed 0.43 Å, indicating that the antiparallel β-barrels arrangement is relatively stable and similar, and does not significantly change in the presence or absence of a ligand/inhibitor.…”
Section: Protein Crystal Structures Analysismentioning
confidence: 99%